Making meaningful data work together. Exploring interoperability, semantic artefacts, and scalable solutions with ATRIUM and LUMEN - Lemoine, Florian; Carloni, Massimiliano; Homo, Julien; Delmazo, Carol; Mystakopoulos, Fotis (Zenodo (CERN European Organization for Nuclear Research), 2026)
In this webinar, Julien Homo and Florian Lemoine of the LUMEN Project and Massimiliano Carloni from the ATRIUM project explore how the work within their respective project helps to pave the way for interoperability, handling semantic artefacts and developing scalable solutions. The webinar took place on the 12th of May 2026.